Autophagy is increased following either pharmacological or genetic silencing of mGluR5 signaling in Alzheimer’s disease mouse models - Khaled S. Abd-Elrahman; Alison Hamilton; Maryam Vasefi; Stephen S. G. Ferguson (Molecular Brain, 2018)
Abstract Alzheimer’s disease (AD) is characterized by neurotoxicity mediated by the accumulation of beta amyloid (Aβ) oligomers, causing neuronal loss and progressive cognitive decline. Genetic deletion or chronic pharmacological inhibition of mGluR5 by the negative allosteric modulator CTEP, rescues cognitive function and reduces Aβ aggregation in both APPswe/PS1ΔE9 and 3xTg-AD mouse models of AD. In late onset neurodegenerative diseases, such as AD, defects arise at different stages of the autophagy pathway. Here, we show that mGluR5 cell surface expression is elevated in APPswe/PS1ΔE9 and 3xTg-AD mice. This is accompanied by reduced autophagy (accumulation of p62) as the consequence of increased ZBTB16 expression and reduced ULK1 activity, as we have previously observed in Huntington’s disease (HD). The chronic (12 week) inhibition of mGluR5 with CTEP in APPswe/PS1ΔE9 and 3xTg-AD mice prevents the observed increase in mGluR5 surface expression. In addition, mGluR5 inactivation facilitates the loss of ZBTB16 expression and ULK1 activation as a consequence of ULK-Ser757 dephosphorylation, which promotes the loss of expression of the autophagy marker p62. Moreover, the genetic ablation of mGluR5 in APPswe/PS1ΔE9 mice activated autophagy via similar mechanisms to pharmacological blockade. This study provides further evidence that mGluR5 overactivation contributes to inhibition of autophagy and can result in impaired clearance of neurotoxic aggregates in multiple neurodegenerative diseases. Thus, it provides additional support for the potential of mGluR5 inhibition as a general therapeutic strategy for neurodegenerative diseases such as AD and HD.